Pengembangan Media Video sebagai Petunjuk Praktikum pada Materi Karbohidrat - Verya Adithya; Masriani Masriani; Maria Ulfah; Rini Muharini; Rody Putra Sartika (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
This research is based on the results of observations of students of chemistry education class of 2020, where students have difficulty in identifying the Benedict and Seliwanoff tests because the test results are similar. This study aims to determine the feasibility level of animated video practicum instructions on carbohydrate material and to find out the response of 2020 class chemistry education students to the animated video media developed. This research is a development research with a modified 4-D model (Define, Design, Development). The subject in this study was an animated video media of practicum instructions on carbohydrate material, which was tested on chemistry education students batch 2020. The data collection instruments consisted of material validation sheets, media validation sheets and student response questionnaires. The developed media obtained material validation results with an average percentage value of 89,5% (very feasible) and material validation with an average percentage value of 92% (very feasible). The test results of the chemistry education student response test class of 2020 to the animated video developed obtained an average percentage value of 90,33% (strongly agree). Based on the results of the research and discussion, it can be concluded that the animated video of carbohydrate practicum instructions is very suitable to be used to overcome the problem of the concept of determining the Benedict and Seliwanoff test.